REPRESENTAÇÕES SÓCIO-RELIGIOSAS DO TRABALHO DOMÉSTICO: UMA LEITURA DE GÊNERO ENTRE BATISTAS NA CIDADE DE SÃO PAULO - Santos, Naira Carla Di Giuseppe Pinheiro dos (2006)
The movements of social plea that had place in years 60 had brought new perspectives for the women, having verified themselves increasing insertion of these in the work market. However, the persistence of the domestic work under dominant responsibility of the women, exactly in this context where the indices of feminine participation in the work market if raise, has called the attention for the subjective constraints and partner-cultural order as decisive elements amongst that they cooperate to the maintenance of this picture. That is, the inequality persists in face of the persistence of sexual hierarchies that continue to delimit the place of the women and that they find in the religions its privileged locus of production and reproduction. It is in the context of the Baptist symbolic economy, where the traditional representations of the man as head and of the woman as help meet , wich means the man as supplier and the woman as wife and mother, responsible for the domestic tasks, that we approach here the problematic one of the sexual division of the work, while and from the practices and representations of Baptists in São Paulo. At the same time where the Baptist s religious speech affirms and ratifies the sexual division of the work, he is subject to the social requests for changes in the gender relations, favoring the mobilization of religious doctrines egalitarians gifts between the Baptists. It is therefore, in a dynamic perspective of tensions between the advances and permanencies in the practical ones of gender to the level of the society amplest, and that they are placed in such a way from the cultural values of this, as much as the material and structural conditions found there, and of tensions between the process of secularization and ethical commitment that the practical and representations of gender searched between the Baptists remain while they change and they advance while they remain.